ChemInform Abstract: A Dramatic Enhancing Effect of InBr3 Towards the Oxidative Sonogashira Cross‐Coupling Reaction of 2‐Ethynylanilines. Issue 25 (June 2016) - Ikeda, A.; Omote, M.; Kusumoto, K.; Komori, M.; Tarui, A.; Sato, K.; Ando, A.
Abstract: The addition of InBr3 to the oxidative Sonogashira reaction of aryl acetylenes (I) and (V) with silane (II) leads to a dramatic increase in reactivity to afford the corresponding 1, 3‐enynes (III) and (VI), respectively.